Regenerative tourism: A bibliometric analysis - Lariza Corral-Gonzalez; Judith Cavazos-Arroyo; Josefa García-Mestanza (Journal of Tourism, Heritage & Services Marketing, 2023)
Purpose: Despite regenerative tourism representing a beacon of hope to fight the problems faced by today's humankind, its multidisciplinary essence and fragmentation hinder the identification of major thematic areas for upcoming researchers. Therefore, the present study aims to systematically review the relevant literature on regenerative tourism. Methods: The literature was revised by adopting a bibliometric protocol. Web of Science and Scopus were employed to access pertinent publications, and Biblioshiny was used to track publication and source evolution and impact, main countries and affiliations' production, authors' relevance, productivity, collaborations, perform content, thematic, and co-citations analyses. Results: The literature on regenerative tourism has recently grown, fostered by rising interest due to the COVID-19 crisis. Attention in the field is still limited to a few main players, requiring an expansion in geographic and academic discipline terms. Thematic areas and their level of development were identified, assessing some relevant topics as fairly unexplored, especially concerning mindset change. Implications: This study offers inferences for future researchers and practitioners, employing literature summarizing, main sources and author identification, as well as gap detection, limiting its results to dual database record retrieval, as well as limited scope or search.
Keywords: L83; Z32; Z1; 330; tourism research; regenerative tourism; conscious tourism; bibliometrics